Aspects of the Self-Help Groups Activities – Italian Experience - Gvaldaitė, Lijana (Acta Paedagogica Vilnensia, 2004)
The article deals with the importance of the self-help groups as a new form of help that has appeared in the world 40–50 years ago, the article analyses the sources of the self-help phenomena and its development in the international context, the typology of the groups is presented. The half-structured interview of qualitative character with the experts and participants of the self-help groups in Lombardy (Italy) is discussed. The research is trying to find out the character of the support received by the Italian families participating in the self-help groups. The research reveals that a self-help group becomes the place where its participants can share needs and experience that protects them from loneliness and social exclusion; the group responds to the essential human need to depend to others, to feel close to the people with the same problems. On the basis of the research we can state that being in a group helps to increase personal maturity and consciousness, stimulates responsibility and independency. Additionally, participation in the self-help group has positive influence upon personal life and interrelations with close people, stimulates openness to the environment, increases social and civil consciousness and activity.